Polymeric nanoparticle vaccines to combat emerging and pandemic threats. (January 2021) - Wibowo, David; Jorritsma, Sytze H.T.; Gonzaga, Zennia Jean; Evert, Benjamin; Chen, Shuxiong; Rehm, Bernd H.A.
Abstract: Subunit vaccines are more advantageous than live attenuated vaccines in terms of safety and scale-up manufacture. However, this often comes as a trade-off to their efficacy. Over the years, polymeric nanoparticles have been developed to improve vaccine potency, by engineering their physicochemical properties to incorporate multiple immunological cues to mimic pathogenic microbes and viruses. This review covers recent advances in polymeric nanostructures developed toward particulate vaccines. It focuses on the impact of microbe mimicry (e.g. size, charge, hydrophobicity, and surface chemistry) on modulation of the nanoparticles' delivery, trafficking, and targeting antigen-presenting cells to elicit potent humoral and cellular immune responses. This review also provides up-to-date progresses on rational designs of a wide variety of polymeric nanostructures that are loaded with antigens and immunostimulatory molecules, ranging from particles, micelles, nanogels, and polymersomes to advanced core-shell structures where polymeric particles are coated with lipids, cell membranes, or proteins. Graphical abstract: Image 1